Effectiveness Of Dynamic Neuromuscular Stabilization Exercise On Reducing Pain In The Elderly With Genu Osteoarthritis - Nurhayati, Shahad Erma; Setiawan, Cahyo; Romadhoni, Dea Linia; Mutnawasitoh, Asita Rohmah (Poltekkes Kemenkes Semarang, 2023)
A pattern of muscle imbalance is seen clinically in osteoarthritis. Quadriceps weakness has been identified as a cause of osteoarthritis in the genu, indicating a link between muscle imbalance and osteoarthritis. The DNS approach aims to exploit brain plasticity and reactivate the patient's dormant natural motor patterns, stimulating global motor reactions and minimizing muscle imbalance. The purpose of this study was to determine the effectiveness of giving dynamic neuromuscular stabilization exercise on pain reduction in the elderly with genu osteoarthritis. This type of research is quantitative: a quasi-experimental pre-post test with a control group design non random sampling with a sample of 50 subjects divided into two groups, namely 25 experimental groups and 25 control groups. The research instruments used closed questionnaires, structured interviews, and pain measurements with NRS. Dynamic Neuromuscular Stabilization Exercise intervention was carried out twice a week for 4 weeks. Data processing in this study used SPSS software program version 26. Data analysis was carried out in the form of a data normality test using the Kolmogorov Smirnov test because the number of subjects was 50 (≥50) people, and the differential effect test used was the Mann-Whitney Test because the data was not normally distributed. The results of this study indicate that there is a difference in influence between the experimental group and the control group of NRS values of p=0.044. There is an effect on the experimental group, and there is a difference in the effect on the experimental group compared to the control group. For future research, it is hoped that if you want to use the same DNS exercise, choose a different dose from this study so that you can see the difference in results and have a newer reference from a different dose.